Reformulation of the Generalized Curvature by Using Decomposition Technique - Tahir H. Ismail; Ibrahim O. Hamad (مجلة التربية والعلم, 2008)
ABSTRACT The aim of this paper is to establish a new formula of generalized curvature discussed with the help of decomposition theorem which is used to obtain generalized curvature for algebraic curves by using some concepts of nonstandard analysis given by Robinson A. and axiomatized by Nelson E.